(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This study assesses the assessed awareness and perceived benefits of Kwara state insurance scheme among residents of Adewole in Ilorin West LGA Kwara state. The study used a descriptive cross-sectional study design. Residents of the Adewole community, which is part of the Ilorin West Local Government Area, participated in this study. For the study on perceptions of Kwara State’s benefits and awareness, a multi-stage sampling technique was employed. Adewole, Ilorin West LGA, Kwara state people are covered by a health insurance program. In the first stage, five villages were chosen at random from the total number of villages in Ilorin West. Additionally, households in the streets of the chosen villages were chosen through systematic random sampling. To guarantee that adults were recruited for the study, respondents were chosen by a purposive method. The data obtained from the study were analyzed using SPSS version 21 (Statistical Package for the Social Sciences). The use of descriptive statistics was made, and frequency tables and percentages were used to present the data. To assess the degree of association between chosen variables at p<0.05, inferential statistics like chi-square were also used. The study reveal that majority of the respondent age fall-within 20-30 years with mean and standard deviation (Mean ± SD) 38 ± 8.9 57.2 percent of respondents were female, 627 percent were married, and 48.5 percent had a healthcare insurance plan. Additionally, this study found that more than half (68.2%) of the respondents were familiar with secondary health insurance coverage and that (74%) of respondents were aware of the Kwara State Health Insurance program. This poll also shows that a majority of respondents (54.3%) had a positive opinion of KSHIS. This survey also identified the challenges faced by KSHIS, such as the attitude of healthcare professionals (64.0%), lack of service (58.3%), high cost of care (51.3%), and delay in acquiring insurance (58.3%), which were all challenges. The majority of respondents (60.2%) had a positive impression of the Kwara Health Insurance Scheme, and the majority of respondents (74.0%) had good awareness of it. This study also demonstrated a substantial relationship between respondents’ perceptions of the state health insurance scheme and their age, gender, and level of education. Adewole inhabitants in the Ilorin West LGA of Kwara State had a mixed understanding of health insurance, though participation was high. To clear obstacles to using and operating the plan, pertinent action should be implemented.